Software tools of teacher’s working time optimization in grading system - Гумен, Олена Миколаївна; Коломієць, Наталія Ярославівна; Смаковська, Ганна Миколаївна; Коломієць, Олена Владиславівна (Technology audit and production reserves, 2013)
The working time of teachers is becoming more intense, and its rational use is very important. The workload is increasing from year to year as a result of increased norms – a number of students per teacher, constant scientific and technological progress and, unfortunately, decreased training level of students at secondary schools. With the introduction of the Bologna system teachers also spend some time calculating the students' grading, while the duration of practical and laboratory classes remains unchanged. To optimize the use of working time a simple, easy to use and universal program for calculating the students’ grading is proposed. The proposed program calculates the total number of points got for each subject, adds bonus points and, depending on the sum of points, determines the corresponding point in the ECTS.